CHARACTERISTIC FEATURES OF APPLICATION OF PSYCHODIAGNOSTIC METHODS IN THE STUDY OF PERSONAL PROTECTIVE MECHANISMS - Karapetyan , M. A. (Արդի հոգեբանություն, 2025)
The article describes the protective mechanisms of the person. A reference is made to the inverse relationship between personal growth and defense mecha- nisms. The topicality of the article is closely connected with its essence and aim, e.i. in psychological consultation, especially in the process of studying the protec- tive mechanisms of the person, the characteristic features of psychodiagnostic me- thods should be strictly taken into consideration, aspiring to the accurate methods of psychological estimation in practical therapy to be considered as a rule, rather than an exception to the rules. It is important to receive initial or accurate infor- mation about the visitor’s personal traits and characteristics by means of psycho- diagnostic testing. The model "Big Five", developed by P. Costa and R. McCray, is presented, which nowadays describes personality traits of people most objectively. It is combined with three-factor model ''Dark Triad' that exposes the dark sides of the person. The need for originality and constant improvement of the source ma- terial is also noted. A reference is made to the main characteristics of the psy- chologist or of the highly skilled person, on the basis of which the specialist is authorized to assemble the mosaic of the mental world of the person in front of him and give a positive result.